Análise da frequência de nevoeiros nos aeroportos de Tucuruí e Carajás - MODESTO, Rodrigo Nielson da Costa (2019)
One of the most important air traffic meteorological elements is the horizontal visibility, which can be affected by the presence of fog at airports and its vicinity, caused danger in the implementation planning of flight of aircraft and its passengers. By reading and decoding METAR data analysis of the frequency of occurrence of fog at airports Tucuruí and Carajás in a period of 5 years (January 2008 to December 2012) was made to understand what time of year this phenomenon weather is more conducive to happen and what local factors influence the formation of fog in southeastern Pará.